Method of evaluation of the quality level of the regenerative anti-wear additives to fuels and lubricants - Фастовець, Павло Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
The method of evaluation of the quality level of regenerative anti-friction anti-wear additives (RAAA) to fuels and lubricants was developed, namely three levels of quality indices of RAAA were adopted; these indices were identified and grouped and formulas for their calculation or scoring were proposed; weight of group indices was defined; the sequence of calculations was determined; the results of laboratory studies, bench and field tests of the additive "RVS PS" were systematized, analyzed and processed; the developed method was tested; specifications of the additive were defined. The relevance of the developed method is caused by the market saturation of RAAA with similar characteristics and different prices. Accordingly, consumers face a problem of choice. One solution to this problem is to substantiate reasonable ‘‘value for money’’, which should be based on the developed method. The sequence of calculations is as follows: first, level III indices are calculated (18 indices, arranged into 6 groups), then - level ІІ indices (group) are calculated as the sum of level III indices in the group and completed by calculating the integral quality index as the sum of six group indices taking into account their weight. Testing of the developed method of evaluation of the quality level of RAAA has confirmed its efficiency and given the quantitative estimate of the quality level of the additive " RVS PS " in the form of the integral index, which was 3.978, and the coefficient of competitiveness was 5.525. It was found that the additive "RVS PS" is the most effective in couplings, joints and assemblies, from 80 % to 100 % worn, and the regeneration degree of the technical condition parameters is about 36 %. If the degree of wear is less than 40%, the regeneration does not occur. The developed method allows to evaluate the quality of other RAAA more objectively than by previously known methods, which will greatly simplify the selection of the most effective additives and indicate the directions of their further improvement, the price of RAAA will correspond to the quality.